1972
DOI: 10.1288/00005537-197210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

High dose pre‐operative radiotherapy and surgery for cancer of the larynx.

Abstract: High dose pre‐operative radiotherapy has played an increasing role in the treatment of advanced cancer of the larynx at the University of Virginia Hospital since 1966. The results of treatment of 72 cases treated in this fashion are compared with 151 cases treated by surgery alone. Employing the actuarial method for calculating survival, there would appear to be a distinct improvement in the group receiving pre‐operative radiotherapy. Local recurrence was reduced to 15 percent following radiotherapy from a lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The distinction between the effects of preoperative and postoperative radiation on development of hypothyroidism has not been characterized in prior studies, and reports are contradictory as to whether preoperative radiation results in more morbidity than postoperative radiotherapy. [20][21][22][23][24][25] Concomitant surgery may interfere with the arterial blood supply and venous drainage to the remaining thyroid lobe, and as a result it may lack sufficient reserves to increase function and produce an adequate supply of thyroid hormone. The unique aspect of this study is that surgical variables remain fairly constant, allowing for a distinction to be made between the effects of preoperative and postoperative radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between the effects of preoperative and postoperative radiation on development of hypothyroidism has not been characterized in prior studies, and reports are contradictory as to whether preoperative radiation results in more morbidity than postoperative radiotherapy. [20][21][22][23][24][25] Concomitant surgery may interfere with the arterial blood supply and venous drainage to the remaining thyroid lobe, and as a result it may lack sufficient reserves to increase function and produce an adequate supply of thyroid hormone. The unique aspect of this study is that surgical variables remain fairly constant, allowing for a distinction to be made between the effects of preoperative and postoperative radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the patients with fistulas received more than the usual dose of 3,000 rads preoperatively. Five cases were subsequently treated for local persistence (I) or distant metastases (4 ) . Two patients had diabetes mellitus and a third developed hepatic failure postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have reported seemingly improved local control, though not always with increased survival, when preoperative radiation was used [Constable et al, 1972;Donald, 1977;Goldman et at, 1972;Hendrickson et al, 1968: Levitt andKing, 1971 ;Krause and McCabe, 1973;Powers and Ogura, 1969;Roswit et at, 1972;Salmo et al, 1977;Sanfillipo et al, 1969;Wanget al, 19721. Equivalent dosages of 3000 rads/3 weeks or less (note that 2000 rads/l week is nearly equivalent to 3000 rads/3 weeks) may have less efficacy than higher dosages [Lawrence et al, 1974;Ogura and Biller, 1970;Powers and Ogura, 19691.…”
Section: Discussionmentioning
confidence: 99%